Administrative obstacles to training female employees - A field study on female administrative staff at Imam Muhammad bin Saud Islamic University – Riyadh - Al-Omar, Hussa Fahad; Al-Askar, Sarah Sami; Al-Tuwaijri, Fatima Abdulaziz (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the organizational, financial and technical obstacles facing the training of administrative staff in Imam Bin Saud Islamic University. The survey descriptive approach has been applied, and the first study results regarding organizational constraints that are limited to participation with external training institutes achieve from training programs provided to female administrative employees. As for financial constraints, the incentive system could not be linked after the courses that the administrative employee obtained from desire and motivation Administrative female employees, and not allocating a budget for the external technical training courses that employing the technology in the training process and publishing it electronically and its weight that benefit from the advantages of technology in providing electronic training opportunities for female administrative employees, and that limited electronic uses for training applications after your use of the technology advantages in remote training for female administrative staff And among the most important elements that concern the measurement of the impact of training on female administrative staff in King Abdullah City for female students at the Imam Muhammad bin Saud Islamic University, and to educate leaders in King Abdullah Female Students University in Imam Muhammad bin Saud Islamic University training for female administrative staff.